Life Perspectives Reflected in the Songs of Khiankhailaewanich: Life Perspectives Reflected in the Songs of Khiankhailaewanich - Kukeati, Chanikant; Khwanthong, Sarinya; Sarapadnuke Chaipunya, Chittapa (RATANABUTH JOURNAL, 2026)
This study aims to analyze the concepts of life reflected in the songs of Khiankhailaewanich published on the artist’s official YouTube platform. The corpus consists of 42 songs released between 2018 and 2025. The data were collected from the complete corpus of songs released during the specified period.This research employed a qualitative research approach, using content analysis as the main method, and the findings were presented through descriptive analysis. The findings reveal that the concepts of life reflected in the songs of Khiankhailaewanich can be classified into seven major themes: time and change, longing and memory, life as a journey, dreams and reality, death, self-healing, and love. The study indicates that the songs of Khiankhailaewanich are not merely works of entertainment, but can also be regarded as contemporary lyrical literature that reflects perspectives on life, impermanence, loss, hope, emotional healing, and acceptance of reality through simple yet meaningful language. This study contributes to the body of knowledge concerning contemporary Thai song literature by demonstrating how popular music functions as a medium for reflecting existential perspectives and human experiences.